Association of genetic variants with autism spectrum disorder in Japanese children revealed by targeted sequencing - Shiota, Yuka; Nishiyama, Tomoaki; Yokoyama, Shigeru; Yoshimura, Yuko; Hasegawa, Chiaki; Tanaka, Sanae; Iwasaki, Sumie; Kikuchi, Mitsuru (Frontiers in Genetics, 2024)
Introduction: Autism spectrum disorders (ASD) represent a heterogeneous group of neurodevelopmental disorders with strong genetic predispositions. Although an increasing number of genetic variants have been implicated in the pathogenesis of ASD, little is known about the relationship between ASD-associated genetic variants and individual ASD traits. Therefore, we aimed to investigate these relationships. Methods: Here, we report a case-control association study of 32 Japanese children with ASD (mainly with high-functioning autism [HFA]) and 36 with typical development (TD). We explored previously established ASD-associated genes using a nextgeneration sequencing panel and determined the association between Social Responsiveness Scale (SRS) T-scores and intelligence quotient (IQ) scores. Results: In the genotype-phenotype analyses, 40 variants of 5 genes (SCN1A, SHANK3, DYRK1A, CADPS, and SCN2A) were associated with ASD/TD phenotypes. In particular, 10 SCN1A variants passed permutation filtering (false discovery rate <0.05). In the quantitative association analyses, 49 variants of 12 genes (CHD8,